PROSES PRODUKSI LAGU “PEACE” DI CITRANALA ART STUDIO - Halawa, Apostolikum Kristian Halawa; Wiyati, Wahyu Sri; Irawan, Ricky (MELODIOUS : JOURNAL OF MUSIC, 2024)
This research aims to find out the procedures, processes and utilization of tools in the production process of the song "Peace" at Citranala Art Studio. According to Sawyer and Golding, music production has 3 general stages, namely: (1) Pre-production (2) Production, (3) Post-production is the last stage which includes the process of editing, balancing, mixing-mastering so that it can present a song that is ready to be presented. The method in this research uses qualitative methods and the data collection techniques are observation, interviews, and documentation. All stages that have been described can be integrated with each other, so that the production completion mechanism on Peace music can be completed properly.